Enhancement of Antifungal Activity of Juglone (5-Hydroxy-1,4-naphthoquinone) Using a Poly(D,L-lactic-co-glycolic acid) (PLGA) Nanoparticle System - Arasoglu, Tulin; Mansuroglu, Banu; Derman, Serap; Gumus, Busra; Kocyigit, Busra; Acar, Tayfun; Kocacaliskan, Ismail (AMER CHEMICAL SOC, 2016)
This study aimed to synthesize and characterize juglone-entrapped poly(D,L-lactic-co-glycolic acid) (PLGA) nanoparticles and compare the antifungal properties of free juglone with its PLGA nanoparticle formulation for the first time. The juglone-loaded nanoparticles prepared using the oil-in-water (o/w) single-emulsion solvent evaporation method were characterized by the reaction yield (RY), encapsulation efficiency (EE), polydispersity index (PDI), particle size, zeta potential (ZP), FT-IR, and in vitro release properties and evaluated for their morphological features using SEM. The nanoparticle formulation had size, RY, ZP, EE,-and PDI values of 212 nm, 66.91 +/- 2.4%, -16.3 +/- 0.7 mV, 70.66 +/- 3.1%, and 0.083 +/- 0.024, respectively. In vitro release showed a triphasic pattern with initial burst followed by sustained release and dormant phase over the study period, releasing about 72.8% in total after 42 days. The antifungal studies against Aspergillus flavus, Candida albicans, and Fusarium spp. using agar dilution and top agar dilution methods indicated that the juglone-encapsulated nanoparticle was more effective than free juglone. This study showed that the top agar method, which was applied for the first time on antifungal activity, is more suitable for the nanoparticular system based on sustained release. Therefore, PLGA nanoparticle formulations may be an important tool for application in many areas for the effective and beneficial use of hydrophobic compounds such as juglone.
Keywords: 5-hydroxy-1,4-naphthoquinone; juglone; nanoparticle; antifungal activity; POLYMERIC NANOPARTICLES; ANTIMICROBIAL ACTIVITY; DRUG-DELIVERY; ITRACONAZOLE; GROWTH; SIZE; MICROPARTICLES; VORICONAZOLE; PARTICLES; STABILITY; Agriculture; Chemistry; Food Science & Technology